Evidence and Graham Harman's Third Table. (1st December 2015) - Ainsworth, Peter
In this article I discuss Larry Sultan and Mike Mandel's Evidence, 1977 contextualized by Graham Harman's text, produced for 'dOCUMENTA(13)', The Third Table, 2012. It is my contention that, although Evidence may have been produced to subvert the modernist tropes of authorship and narrative, or to draw our attention to visual material, which is 'ready-to-hand', the photographs can also be explored as a visual metaphor for Graham Harman's approach to Object-Orientated Ontology (OOO). I seek to demonstrate that there is significance in analysing the work in the context of Harman's description of relations, his concepts of 'overmining' and 'undermining' and debates surrounding 'OOO'. The article is a reading of the photographs, where the caption-less, unreferenced images, selected by Sultan and Mandel from various institutions and recontextualized in relation to art, are explored through ideas contained in Harman's short text.